'Car Talk': automobility and Chinese international students in Michigan. Issue 2 (4th March 2019) - Louie, Andrea; Qin, Desiree Baolian
ABSTRACT: The apparent conspicuous consumption of luxury vehicles by Chinese international students attending a public Michigan University provides an opportunity to examine the convergence of different ideas about automobility. Upwardly mobile Chinese families send their children to Michigan, a state with a tradition of auto-production, for educational opportunities not available in China. The resulting 'car talk' of local residents about Chinese students and their cars speaks to broader anxieties about Michigan's shifting relationship to the global economy. However, the paper focuses on the meanings of auto-owning created by Chinese students who make decisions about the purchase and use of their autos within a social world oriented primarily to other Chinese students and societal ideas about auto-owning circulating among friends, family and society in China. For Chinese students, car owning encompasses meanings of status, safety and sociability that are created within the context of study abroad.